Holocene Lake Evolution and Glacial Fluctuations Indicated by Carbonate Minerals and Their Isotopic Compositions in the Sediments of a Glacial Melt Recharge Lake on the Northwestern Tibetan Plateau - Li, Minghui; Zhu, Liping; Wang, Junbo; Ju, Jianting; Liu, Chong; Ma, Qingfeng; Xu, Teng; Qiao, Baojin; Wang, Xiaoxiao (Frontiers in Earth Science, 2021)
Lakes and glaciers are widely distributed on the Tibetan Plateau and are linked via hydrological processes. They are experiencing rapid changes due to global warming, but their relationships during the Holocene are less well known due to limited coupled geological records. Here, we analyzed the δ13C-VPDB and δ18O-VPDB values and ion content of calcite and aragonite in a 407-cm-long sediment core from Guozha Co, a closed basin on the northwestern Tibetan Plateau supplied by glacial meltwater, in order to understand how the lake responded to glacier changes during the Holocene. Our results indicate that the glacial meltwater lowered the lake’s temperature and the δ18Olake water and δ18Oendogenic + authigenic carbonate values and diluted the ion concentrations in the lake water. Three stages of evolution, 8.7–4.0, 4.0–1.5, and 1.5 kyr BP to present, are distinguished based on the decrease in glacial meltwater recharge. Guozha Co has been a closed basin since at least 8.7 kyr BP, and it has changed from a fresh water lake during 8.7–1.5 kyr BP to a brackish lake from 1.5 kyr BP to present due to several climate events. The famous 4.2 kyr BP cold event was identified in the core at 4.0 kyr BP, while warm events occurred at 6.2, 3.9, 2.2, 0.9, and 0.4 kyr BP. Both glaciers and lakes in this area are controlled by climate, but they exhibit opposite changes, that is, glaciers retreat and lakes expand, and vice versa. Our results provide an accurate interpretation of the cold events based on carbonate minerals and carbon–oxygen isotopes in glacial meltwater–recharged lake sediments.